2020
DOI: 10.1007/s00234-020-02369-0
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal degree centrality in delayed encephalopathy after carbon monoxide poisoning: a resting-state fMRI study

Abstract: Purpose To explore neuropathologic mechanisms in functional brain regions in patients with delayed encephalopathy after carbon monoxide poisoning (DEACMP) from the perspective of the brain network nodes by resting-state functional magnetic resonance imaging (rs-fMRI). Methods The fMRI and cognitive assessments were performed in 25 patients with DEACMP and 25 age-, sex-and educationmatched healthy controls (HCs). Data analysis was performed via the degree centrality (DC) method. Then, the associations between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
12
1
Order By: Relevance
“…Additional previous studies have found that DC differed between in psychiatric disorders; One study demonstrated that DC changes in the hippocampus are related to delayed encephalopathy after carbon monoxide poisoning (DEACMP). Compared with healthy controls, DEACMP patients with cognition disturbances displayed significantly decreased DC values in the right hippocampus but increased DC values in the right inferior frontal gyrus, which is inconsistent with our results (Wu et al, 2020 ). This inconsistency may be related to differences in characteristics or diseases, but can also indicate that abnormal brain function in the hippocampus may present as changed DC.…”
Section: Discussioncontrasting
confidence: 99%
“…Additional previous studies have found that DC differed between in psychiatric disorders; One study demonstrated that DC changes in the hippocampus are related to delayed encephalopathy after carbon monoxide poisoning (DEACMP). Compared with healthy controls, DEACMP patients with cognition disturbances displayed significantly decreased DC values in the right hippocampus but increased DC values in the right inferior frontal gyrus, which is inconsistent with our results (Wu et al, 2020 ). This inconsistency may be related to differences in characteristics or diseases, but can also indicate that abnormal brain function in the hippocampus may present as changed DC.…”
Section: Discussioncontrasting
confidence: 99%
“…Third, the statistical correction method we used is a cluster-defining-threshold (CDT) approach, which might import potential false positive rates. However, we set the voxel-level p < 0.001 and cluster-level p < 0.05 as the previous studies used ( Eklund et al, 2016 ; Lin et al, 2019 ; Yang et al, 2019 ; Wang et al, 2020 ; Wu et al, 2020 ) to reduce the false positive rate as much as possible. Future studies are required to verify the results with a larger sample size and different statistical correction methods.…”
Section: Discussionmentioning
confidence: 99%
“…The cells release excitatory transmitters, loss of calcium ions, and ultimately activation of the apoptotic cascade of cell activation ( Douglas-Escobar and Weiss, 2015 ). However, more studies have been conducted on delayed encephalopathy following acute CO poisoning ( Hou et al, 2013 ; Lee et al, 2018 ; Wu et al, 2020a , b ), in which the main pathological changes are extensive demyelination of the brain’s white matter, bilateral symmetrical pallidocyte ischemia, and necrosis. There are only a few studies on brain function alterations during the acute phase of CO poisoning ( Dinghua et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%